Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan Bagian Produksi pada PT. Agri Lestari Nusantara - Kalvin Graha Aristanora; Toton (Jurnal EMT KITA, 2023)
This study was conducted at PT. Agri Lestari to study the impact of training and work motivation on employee performance. The research method used is quantitative using a variety of linear analysis techniques. The study respondents were 50 employees from PT's production team. Agri Lestari Nusantara, selected by saturation sampling. Data checking was performed using SPSS 26.0 software. The results of data analysis show that training has a positive and significant impact on employee performance. In addition, work motivation also has a positive and significant impact on employee performance. At the same time, training and motivation at work has a positive and significant impact on employees. This study provides valuable information for PT. Agri Lestari in improving employee performance through training efforts and increasing work motivation.